Civil-Military Relations in China: An Obstacle to Constitutionalism? - Paltiel, Jeremy T. (Columbia Journal of Asian Law, 1995)
The armed forces have three massive political advantages over civilian organizations: a marked superiority in organization, a highly emotionalized symbolic status, and a monopoly of arms. They form a prestigious corporation or Order, enjoying overwhelming superiority in the means of applying force. The wonder, therefore, is not why this rebels against its civilian masters, but why it ever obeys them. A standing army can pose a threat to the stability of any civilian regime. Constitutional regimes have evolved legal mechanisms to assure the subordination of the military to civilian authorities. However, given the advantages of the military in terms of both physical force and organization noted by Finer above, restraining military power requires much more than legal texts. When armed force was used to reassert authority in June 1989, the Communist Party of China demonstrated the paramount importance of the role that civil-military relations play in the current regime. Civilian control is both a matter of the organization of civil society in a manner which neutralizes the organizational advantages of the military, as well as of the subjective inculcation of a military ethic to habituate the military to civilian control. As observed by Tuan-sheng Ch’ien, there is a tendency for the military to idealize obedience, all the while recognizing their pivotal role in government. The way then to diminish military dominance in times of peace is to develop a political force with equal or greater organization and power than the military. This article begins with a discussion of various ideals of constitutionalism and of civil-military relations thereunder. The focus then turns to the status of civil-military relations in pre-revolutionary, revolutionary, and modem China. Finally, this article explores the relationship between the Chinese Communist Party (the “CCP” or the “Party”) and the Chinese armed forces, the People’s Liberation Army (the “PLA”) and its affiliated paramilitary police, the People’s Armed Police, with a view to establishing the minimum conditions under which civil-military relations in China could be made to conform to constitutional rule.